FAKTOR-FAKTOR YANG MEMPENGARUHI INTENSI WHISTLEBLOWING DENGAN DILEMA ETIKA SEBAGAI VARIABEL PEMODERASI - Agustiani, Rafika; Lestari, Puji; Arofah, Triani (Program Studi S1 Akuntansi Fakultas Ekonomi & Bisnis Univesitas Jenderal Soedirman, 2019)
This study aims to determine the effect of organizational commitment, personal cost, personal responsibility,and the level of fraud, on the intention of whistleblowing with ethical dilemmas as moderating variables in the Inspectorate District and Pekalongan City. The population in this study were all Pekalongan District Inspectorate staff and Pekalongan City Inspectorate with a total population of 69. The sample of this study amounted to 32 obtained from the determination of samples using purposive sampling method with criteria namely Inspectorate employees who served as functional employees consisting of P2UPD, Auditors, and general functional / other staff, in this case there are 19 functional employees of the Pekalongan District Inspectorate and 13 functional employees of the Pekalongan City Inspectorate. The results of this study indicate that: (1)Organizational commitment has no significant effect on whistleblowing intentions; (2) Personal costs have a significant effect on whistleblowing intentions; (3) Personal responsibility has a significant effect on whistleblowing intentions; (4) The level of fraud has a significant effect on whistleblowing intentions; (5)Organizational commitment, personal cost, personal responsibility, and fraud level have a significant effect on whistleblowing intentions; (6) The ethical dilemma is not able to moderate the influence of organizational commitment, personal cost, personal responsibility, and the level of fraud on whistleblowing intentions at the Inspectorate District and Pekalongan City.